THE SOCIAL ESSENCE OF GENDER IDENTIFICATION AND THE PROBLEM OF GENDER EQUALITY IN UZBEKISTAN - D.M.Mahmudova (Western European Studies, 2025)
This article analyzes the essence of the concept of gender identity, its introduction into science, gender equality, and gender equality relations in social life in the Republic of Uzbekistan.
Keywords: Gender identity; gender equality; human rights